Electrical, electromagnetic shielding, and some physical properties of hybrid yarn-based knitted fabrics - Bedeloğlu, Ayşe (Taylor & Francis Ltd, 2013)
Recently, increasing number of studies are performed on protective fabrics containing metal wires for electromagnetic shielding purposes. In the present paper, the hybrid fabrics in plain and rib structures were knitted by using single and double ply hybrid yarns obtained by acrylic (PAC) yarns plied with stainless steel wires having two different diameters. The physical properties including conductivity, air permeability, pilling, and abrasion resistance as well as electromagnetic shielding effectiveness (EMSE) were measured. The variations in EMSE as well as reflection, absorption, and transmission and in other physical properties of knitted hybrid fabrics were investigated considering wire content and weave structure. It was seen that an increase in the wire content significantly increased the conductivity. Rib fabrics exhibited better EMSE values as compared with plain fabrics. Fabrics using two-folded yarns exhibited better EMSE values. Fabrics using thinner wire exhibited higher EMSE values. The highest EMSE value was obtained for rib-knitted fabric with 35 micrometer (m) stainless steel wire.
Keywords: acrylic; conductivity; electromagnetic shielding effectiveness; hybrid yarn; knitted fabric; stainless steel wire